PLATELET SPLEEN INDEX IS A NONINVASIVE TECHNIQUE TO DETECT ESOPHAGEAL VARICES IN CIRRHOTICS - KHAN , S; AMAR , H; MUNEEB , A (Biological and Clinical Sciences Research Journal, 2024)
Esophageal varices (EV) are a common complication in cirrhotic patients, and early detection is crucial to prevent variceal bleeding. Traditionally, the diagnosis of EV requires invasive procedures such as endoscopy. The Platelet Spleen Index (PSI), a noninvasive method, has shown promise in identifying patients with EVs. Objective: To assess the role of the Platelet Spleen Index in detecting esophageal varices in cirrhotic patients and compare its diagnostic accuracy to traditional invasive methods. Methods: A total of 1000 cirrhotic patients were included in this study. Each patient underwent an abdominal ultrasound to measure spleen size and a complete blood count to determine platelet count. The Platelet Spleen Index (PSI) was calculated using the formula: PSI = (Spleen diameter in cm × Platelet count) / 1000. Endoscopy was performed on all patients to assess the presence and grade of esophageal varices directly. The diagnostic performance of PSI was analyzed using receiver operating characteristic (ROC) curves, sensitivity, specificity, and positive/negative predictive values. Results: The PSI value demonstrated a significant correlation with esophageal varices, with an optimal cutoff of ≤1.2 predicting the presence of varices. At this threshold, PSI exhibited a sensitivity of 88% and specificity of 79%. Positive predictive value (PPV) and negative predictive value (NPV) were calculated as 85% and 81%, respectively. ROC analysis revealed an AUC of 0.89, highlighting the high diagnostic accuracy of PSI in identifying esophageal varices. Furthermore, PSI was significantly correlated with variceal grade, with lower PSI values associated with higher varice grades. Conclusion: The Platelet Spleen Index is a reliable, noninvasive method for detecting esophageal varices in cirrhotic patients. This technique offers a valuable alternative to endoscopy, particularly in resource-limited settings or in situations where endoscopic screening is not immediately available.